Interaksi Sosial Virtual dalam Permainan Among Us Indonesia - Dheny Yori Putra; Zainal Abidin Achmad (Program Studi Ilmu Komunikasi Fakultas Dakwah dan Komunikasi, UIN Sunan Ampel Surabaya, 2022)
Among Us is a virtual game that requires players to fill certain roles. This game forms interactions virtually between individuals in the Among Us game on the Discord application. The focus of this research is virtual social interaction on the Discord application of the game Among Us Indonesia. This study uses a qualitative method with a virtual ethnographic approach. The results of the study show that positive associative social interaction is more dominant than the negative one among the players of the game. Factors supporting this domination of social communication are age and motivation to join the community. Although the social interaction only occurs virtually, the members have experienced an increase in the ability to interact and communicate socially both speaking and writing skills. In addition, there has been positive growth with regard to general knowledge and social awareness amongst the players.